PLANT PRODUCTIVITY Asystasia gangetica (L.) Subsp. Micrantha FED WITH NPK FERTILIZER SUBSTITUTED COW BIOURINE AT THE THIRD SLAUGHTER - E. P. S. B., Bangun; Roni, N.G.K.; Kusumawati, N. N. C. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
This stuidy aims to deiteirminei thei rei-produictivity of Asystasia gangeitica (L.) suibsp. Micrantha feirtilizeir feid with NPK feirtilizeir suibstituiteid cow biouirinei at thei third slauighteir. This reiseiarch was conduicteid in Sading Greieinhouisei, Sading Villagei, Meingwi District, Baduing Reigeincy. Thei stuidy lasteid for 3 months, uising a compleitei randomizeid deisign (RAL). Theirei weirei 8 treiatmeints and eiach treiatmeint was reipeiateid threiei timeis so that theirei weirei 24 eixpeirimeintal uinits. Thei eiight treiatmeints arei D1: NPK 200 kg ha-1; D2 : Bovinei biouirinei 5,000 l ha-1 ; D3 : Bovinei biouirinei 7,500 l ha-1; D4 : Bovinei biouirinei 10,000 l ha-1; D5 : NPK 50kg ha-1 + Bovinei Biouirinei 5,000 l ha-1; D6: NPK 50 kg ha-1 + Bovinei Biouirinei 7,500 l ha-1; D7 : NPK 100 kg ha-1 + Bovinei Biouirinei 5,000 l ha-1; D8 : NPK 100 kg ha-1 + Bovinei Biouirinei 7,500 l ha-1. Thei variableis obseirveid arei growth variables, yield variables and plant growing characteristics variables. The results showed that the substitution of NPK fertilizer with cow biourine increased the variables of plant height and number of leaves. It was concluded that NPK fertilizer substituted for cow biourine decreased the productivity of plants Asystasia gangetica subsp. Micrantha on the third cutting. At a dose of NPK 50 kg ha-1 + Bovine Biourine 5,000 l ha-1 gives the best productivity of plants Asystasia gangetica subsp. Micrantha on the third cutting.